The fate of the mentally ill during the Second World War (1940–1945) in Troms and Finnmark, Norway - Fause, Åshild (Nordlit, 2015)
The article analyses the fate of the mentally ill living in northern Norway during the 2nd World War, and the way the war changed their lives. The study is the first to give a systematic account of how the mentally ill fared during the deportation of Finnmark and Northern Troms and afterwards. The reader is introduced to the general conditions for mentally ill persons living in the north, their households and communities, the mental care systems and psychiatric institutions. The article also draws comparisons between Nazi politics and actions towards mentally ill in Norway and Germany. The article is an important contribution to an understanding of the impact of war and deportation on this part of the population.